Practical TCP - Reynders, Deon (Elsevier, 2003)
TCP/IP (Transmission Control Protocol/Internet Protocol) is the suite of communications protocols used to connect hosts on the Internet. TCP/IP uses several protocols, the two main ones being TCP and IP. TCP/IP is built into the UNIX operating system and is used by the Internet, making it the de facto standard for transmitting data over networks. The TCP/IP suite of protocols has become a dominant technology due to its widespread use and reliability, while Ethernet is fast becoming a de facto industrial networking standard. * A practical hands-on book that.